Informacijos šaltinių naudojimas Lietuvos vietiniuose laikraščiuose pateikiant piniginės socialinės paramos skirstymo pertvarkos aktualijas: žurnalistų profesionalizacijos prielaidos - Donauskaitė, Džina (Information & Media, 2014)
Šiame straipsnyje, išanalizavus šiuolaikines žurnalistinio profesionalumo sampratos kaitos struktūrines prielaidas ir naujas profesionalizacijos kryptis informacijos šaltinių naudojimo aspektu, atskleidžiamos Lietuvos vietinės spaudos žurnalistų informacijos šaltinių naudojimo tendencijos. Tiriamas žurnalistų informacijos šaltinių naudojimas pateikiant 2012 m. penkių rajonų savivaldybėse įgyvendintą piniginės socialinės paramos skirstymo pertvarką, kuri buvo dabar jau nacionaliniu mastu vykdomos skurdo mažinimo politikos reformos (decentralizacijos) eksperimentinis etapas. Taikant tinklo analizės metodą atskleidžiama, jog vietinės spaudos žurnalistų tinklas yra siauras, o informacijos šaltinių diversifikacija naujomis profesionalizacijos kryptimis yra maža. Tai rodo nepakankamą vietos žurnalistų profesionalumą, kuris jau netrukus gali tapti kliūtimi užtikrinant analizuotų žiniasklaidos organizacijų veiklos tęstinumą.Reikšminiai žodžiai: žurnalistų profesionalumas, profesionalizacija, informacijos šaltinių įvairinimas, piniginė socialinė parama, vietinė spauda.Lithuanian local media’s sourcing of information about on-going changes in cash social assistance distribution: assessment of the professionalization of journalistsDžina DonauskaitėSummaryThe article presents an analysis of change of the liberal concept of journalistic professionalism and its structural premises. Drawing on the notion of journalistic professionalism not only as a normative but also as an analytic category, it claims that, despite the growing importance of the quantitative value of information in the contemporary media market, the high level of the professionalism needs to be considered as one of the preconditions for sustaining a successful and competitive media business. The need for the new four directions of journalistic professionalization with respect to the sourcing of information at the level of local media is formulated: 1) diversification of sources according to their decision-making power; 2) diversification of sources according to their position in the societal structure; 3) diversification of sources according to their distance; 4) diversification of sources according to their competences and experiences. Selected for empirical analysis are five local newspapers that were mediating the on-going changes in cash social assistance distribution in five Lithuanian rural municipalities. The main questions that have been guiding the empirical study were: 1) what the network of information sources used by local journalists consists of? 2) how are information sources in the network connected to each other? 3) do local journalists diversify their sources according to the new four directions defined in the theoretical analysis of the article? The results show that diversification is very limited – journalists rely on sources from local government, almost do not cite the interest groups involved in policy making, completely ignore scientists and other experts, although citing some affected welfare recipients and national-level sources. Overall, the networks of sources for local media journalists are very narrow. Therefore, it is discussed in the concluding remarks of the article whether these results might be interpreted as a signal of the impending and inevitable decline of the analysed local media in the nearest future.